2010
DOI: 10.1177/1012690210362027
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between community sport clubs and social capital in Japan: A comparative study between the comprehensive community sport clubs and the traditional community sports clubs

Abstract: Social capital has been emphasized as a way to solve various community problems, and sports are considered one way to build social capital as a catalyst for that purpose. Comprehensive community sport clubs offer not only various sports but also opportunities for communication among club members. However, most traditional community sports clubs are designed for only one type of sport, and their scope is limited in terms of gender, age, and technique. This study compares the varieties of community sport clubs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 38 publications
0
34
0
1
Order By: Relevance
“…Community level analyses examine the collective good produced through ties between individuals [19]. Focus is often placed on the number of voluntary associations [20] and measures of general levels of trust [21]. The distinction between the individual and collective levels is a matter of emphasis, as social capital can be accrued at both levels and as both levels are mutually reinforcing [22].…”
Section: Social Capital Accrual Among African Americansmentioning
confidence: 99%
“…Community level analyses examine the collective good produced through ties between individuals [19]. Focus is often placed on the number of voluntary associations [20] and measures of general levels of trust [21]. The distinction between the individual and collective levels is a matter of emphasis, as social capital can be accrued at both levels and as both levels are mutually reinforcing [22].…”
Section: Social Capital Accrual Among African Americansmentioning
confidence: 99%
“…They may be applicable to sports clubs in other Western European countries since they were found to have similar financial circumstances despite different policy systems [50]. The generalizability of findings may be extended to comprehensive community sports clubs in Japan that also offer sport and non-sport programs [51] indicating similarities to the Western European sport club system. The results may also inform sport and recreation organizations in Canada that serve a variety of population groups [52].…”
Section: Resultsmentioning
confidence: 78%
“…A more recent study by Walseth (2008) highlighted that young Muslim women can benefit as individuals through the establishment of social networks via involvement in sport but that there was little evidence that the value of such networks aggregate to benefit a community. Okayasu et al (2010) found that Japanese comprehensive sport clubs (similar to Westernized sport clubs offering multiple sports) were better at fostering social capital than their traditional instrumentally focused sport club counterparts.…”
Section: Social Capital and Sportmentioning
confidence: 97%